Proposta de ensino de tabela periódica - uma abordagem alternativa a partir da História da Ciência - Espir, Iago Ferreira (2021)
The research presents a didactic sequence proposal (SD) for Chemistry classes in first year classes of High School of a public school in Uberaba-MG on the content Periodic Table (TP) using aspects of its history, elaborating an educational product that can be reproduced or used as an aid by any teacher. In this way, a research was carried out that proposed a reflection on the so-called “traditional teaching” of TP and, from that, mount an alternative approach using the History of Science (HC). The research was divided between: seeking, through bibliographic review, a more accurate view of the construction / development of TP, as well as its use as a tool to describe the Periodic Law and study the Periodic Properties; do, also through bibliographic review, an analysis of the use of HC in Chemistry classes; to elaborate, based on the understanding of the depth about TP and the interface between HC and Chemistry Teaching, a proposal for SD for TP classes with an approach that uses HC. With this, a deeper and more contextualized approach to TP classes is presented. Due to the SARS-CoV-2 pandemic period since March 2020, classes in Minas Gerais took place remotely, which influenced the execution of the SD and the percentage of students who participated in all the proposed activities; even so, SD was able to contribute to 1) students have a better understanding of the concepts worked on seeing their elaboration and transformation over time; 2) students understand scientific practice and; 3) students have a more human view of scientists, having them as subjects who live in their own times and contexts.